(untitled) (Takwil: Journal of Quran and Hadith Studies, 2025)
This research aims to explore the holistic meaning of Asbab al-Nuzul of educational verses as a guide in addressing the crisis of the chain of knowledge transmission caused by artificial intelligence (AI), which increasingly reduces the role of teachers. The urgency of this research lies in the role and responsibility of Islamic education in shaping the character of students in the presence of AI, particularly concerning these issues. This study is designed using a descriptive qualitative method, utilizing library research as the primary source. The current moral shift away from Qur’anic values is not surprising. Therefore, to cultivate good character in students, the presence of humans as role models, inspirators, motivators, and facilitators is required, and it is not sufficient through AI technology alone. Keywords: Asbab al-Nuzul, Educational Verses, Artificial Intelligence, Character Education.